Treasury Bill Auctions : Issues and Uses - Cottarelli, Carlo (IMF Working Papers; Working Paper ;, 1994)
We review the main issues that arise in the design of treasury bill auctions and survey the relevant empirical literature. We also provide a detailed description of the actual design of these auctions in a sample of 42 industrial and developing countries.